Determinants of the Success of Da'wah: Analysis of Indonesian Manuscripts - Abdullah Mubarok; Efri Syamsul Bahri; Mohd Mizan bin Mohammad Aslam (Alhadharah: Jurnal Ilmu Dakwah, 2023)
Since the time of the Prophet Muhammad, da'wah has been running with various dynamics it faces. However, studies on the success factors of da'wah from time to time still need to be completed. This study aims to explore the determinants of the success of da'wah. The literature research data were sourced from Google Scholar. Data collection using the publish or perish application from Indonesian Manuscripts. Data analysis used the preferred reporting items for systematic reviews, meta-analyses (PRISMA), and bibliometric approaches. The study identified six indicators of da'wah's success: aqidah, morals, benefit, welfare, happiness, and change. Then, this study found five success factors of da'wah: knowledge, faith, charity, leadership, and means. Finally, this research also produced a conceptual model that determines the success of da'wah. Da'wah organizations can respond to the results of this study by increasing their contribution to the five success factors of da'wah